Claustrophobia and adherence in magnetic resonance imaging procedure - Grilo, Ana Monteiro (2013)
Claustrophobia causes a huge discomfort to those who need to perform Magnetic Resonance examinations mainly due to the physical design of most equipment. This study aimed to maximize the success rate of Magnetic Resonance Imaging (MRI) clinical studies in claustrophobic patients by the identification of facilitative strategies.